PENERAPAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 SOMAMBAWA - Oniati Gea; Baziduhu Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This study was motivated by low student engagement in the learning process, which resulted in low achievement in economics learning outcomes among Grade X students at SMA Negeri 1 Somambawa. The purpose of this study was to examine the implementation of the Numbered Heads Together (NHT) learning model in economics classes and to determine the improvement in students’ learning outcomes after applying the model. This research employed a Classroom Action Research (CAR) design conducted in two cycles. The research subjects were 25 students of class X-III, consisting of 9 male and 16 female students. Data were collected through observations of teacher activities, student activities, and learning outcome tests. The results indicated improvement in each cycle. Teacher activity increased from 61.3% in Cycle I to 84% in Cycle II, while student activity increased from 60.22% to 94.3%. Student learning mastery improved from 64% in Cycle I to 100% in Cycle II, meeting the predetermined minimum mastery criteria. Therefore, it can be concluded that the implementation of the Numbered Heads Together learning model effectively improved students’ economics learning outcomes. Teachers are encouraged to continuously innovate in instructional strategies to enhance both the learning process and outcomes.